In vitro bioaccessibility of β-carotene in pumpkin and butternut squash subjected to different cooking methods - Koh, S. H.; Loh, Su Peng (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2018)
β-carotene, a type of provitamin A, is beneficial to our health. However, the compound needs to be released from its food matrix before being utilised by the body. Thus, understanding the bioaccessibility of β-carotene in the food consumed is a crucial step. The objective of this study was to determine the effect of various cooking methods on bioaccessibility of β-carotene in pumpkin and butternut squash. In vitro digestion was carried out on raw and cooked (steamed, boiled, and deep-fried) pumpkin and butternut squash. β-carotene was identified using RP-HPLC. Generally, butternut squash (4.99±0.02mg/100g) had higher β-carotene content than pumpkin (4.34±0.04mg/100g). Thermal processing resulted in lower β-carotene content in pumpkin samples; however, it increased the β-carotene content in butternut squash samples. In term of bioaccessibility, thermal processes increased the percentage of bioaccessible β-carotene in both pumpkin and butternut squash samples. Raw pumpkin had 10.56±0.44% of bioaccessible β-carotene while raw butternut squash had only 1.65±0.04%. Bioaccessibility of β-carotene in deep-fried pumpkin and butternut squash were significantly higher than their raw sample with 68.86±0.86% (p<0.001) and 22.32±2.12% (p<0.05) of bioaccessible β-carotene respectively. The deep-frying method was found to enhance the bioaccessibility of β-carotene significantly in both of these samples but not boiling and steaming methods.